2011
DOI: 10.1111/j.1600-0501.2011.02202.x
|View full text |Cite
|
Sign up to set email alerts
|

Deproteinized bovine bone mineral in marginal defects at implants installed immediately into extraction sockets: an experimental study in dogs

Abstract: The application of DBBM concomitant with a collagen membrane to fill the marginal defects around implants placed into the alveolus immediately after tooth extraction contributed to improved bone regeneration in the defects. However, with regard to buccal bony crest preservation, a limited contribution of DBBM particles was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
66
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 33 publications
14
66
1
2
Order By: Relevance
“…Interestingly, enhanced bone preservation was found when using deproteinized bovine bone mineral particles and a collagen membrane compared to controls whereas no such benefit was noted when using magnesium-enriched hydroxyapatite [99101]. Recently Araújo and coworkers have evaluated the use of Bio-Oss Collagen in the volume between the buccal wall and the implant in cases treated with immediate implant placement in an experimental animal model.…”
Section: Rationale For Extraction Socket Preservationmentioning
confidence: 99%
“…Interestingly, enhanced bone preservation was found when using deproteinized bovine bone mineral particles and a collagen membrane compared to controls whereas no such benefit was noted when using magnesium-enriched hydroxyapatite [99101]. Recently Araújo and coworkers have evaluated the use of Bio-Oss Collagen in the volume between the buccal wall and the implant in cases treated with immediate implant placement in an experimental animal model.…”
Section: Rationale For Extraction Socket Preservationmentioning
confidence: 99%
“…This corresponds to a bone atrophy of 25% [26]. Furthermore, buccal alveolar bone resorption between 1.8 and 2.1 mm in both, DBBM treated and untreated extraction sockets, was shown in dogs 4 months after tooth extraction [27].…”
Section: Discussionmentioning
confidence: 97%
“…In another experimental study Caneva et al [20] explored the effect of GBR based on deproteinized bovine bone mineral on alveolar ridge preservation and the reparation of defects around osseointegrated implants. The authors concluded that the application of DBBM concomitant with a collagene membrane contributed in improving bone regeneration in the defects.…”
Section: Literature Reviewmentioning
confidence: 99%